Characterization of volatile aroma compounds after in-vial cooking of foxtail millet porridge with gas chromatography-mass spectrometry. (July 2018) - Zhang, Yiru; Yang, Ni; Fray, Rupert G.; Fisk, Ian; Liu, Chujiao; Li, Hongying; Han, Yuanhuai
Abstract: Foxtail millet has become popular over recent years for its nutritional value and ecological functions. The aroma of foxtail millet is not well characterized, which is critical for its eating quality and understanding the biochemistry and genetics of aroma is important for molecular breeding of millets rich in aroma. In this study, the volatile aroma compounds of the elite millet variety Jingu 21 were investigated at different cooking times, pH, processing methods, and compared with 3 other varieties. An in-vial cooking method was developed which combined solid phase micro-extraction and gas chromatography-mass spectrometry for the detection and identification of volatile compounds. The main findings were: a) Twelve aroma compounds were identified during cooking, which were hexanal, heptanal, octanal, (E)-2-heptenal, nonanal, trans-2-octenal, trans-2-nonenal, 2, 4-nonadienal, (E, E)-2, 4-decadienal, 1-octen-3-ol, 2-pentylfuran and 6-methyl-5-hepten-2-one. b) Longer cooking times produced higher concentrations of aroma compounds. c) Variations in cooking pH (from 6 to 8) had no obvious impact on the aroma of the millet porridge. d) More volatile compounds were released from millet flour compared to millet grain. e) There were significant differences among varieties and Jingu 21 millet showed the highest abundance of most aroma compounds, explaining partly why it is strongly favored by consumers for decades. Highlights: An in-vial cooking was developed to analyse aroma compounds in foxtail millet. Within 40 min, longer cooking times result in higher levels of volatiles. More aroma compounds were released from millet flour than grain during cooking. Popular variety Jingu21 released higher levels of aroma compounds than the others.